Real-world experience with selinexor-containing chemotherapy-free or low-dose chemotherapy regimens for patients with relapsed/refractory acute myeloid leukemia and myeloid sarcoma - Tong, Xiwen; Jin, Jie; Xu, Bin; Su, Shuai; Li, Li; Li, Mengyuan; Peng, Yizhou; Mao, Xia; Huang, Wei; Zhang, Donghua (Frontiers in Pharmacology, 2023)
Treatment of relapsed or refractory acute myeloid leukemia (R/R AML) and myeloid sarcoma (MS) has presented challenges for decades. Studies on selinexor in combination with various standard or intensive chemotherapy regimens for the treatment of R/R AML have demonstrated promising results.Our study demonstrated real-world clinical experience using chemotherapy-free or low-dose chemotherapy regimens containing selinexor in R/R AML and MS patients and included 10 patients.All patients were evaluable for response, achieving CR in four (40.0%) patients and CRi in two (20.0%) patients for a total CR/CRi of 60.0%. The ORR was 80.0% when patients with PR were included. Five (50.0%) patients underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) after treatment with selinexor-containing regimens. At the end of the follow-up, seven (70.0%) patients were alive, and three patients died of transplant-related complications or disease progression. The most frequently reported nonhematologic adverse events (AEs) in patients were grade 1 or 2 asymptomatic hyponatremia. The chemotherapy-free or low-dose chemotherapy regimens in combination with selinexor for R/R AML are feasible and tolerable and provide an opportunity for patients to receive transplantation.